The Relation Between Price, Online Reviews, Consumer Trust, and Purchase Decisions for OMG Lipmatte Products on the Shopee Platform - Pipit Putri Mayangsari; Khaerudin Imawan; Aghnia Dian Lestari (Cv. Syntax Corporation Indonesia, 2026)
Current consumer behavior has been influenced by advances in digital technology and the increased use of e-commerce platforms in making purchasing decisions, especially for cosmetic products. As a leading marketplace in Indonesia, Shopee offers various features, such as competitive prices, online reviews, and transaction systems that help build consumer trust. This study aims to analyze the relationship between price, online reviews, and consumer trust and purchasing decisions for OMG Lipmatte products on the Shopee platform among 12th-grade students at SMAN 1 Cibingbin. This study uses a quantitative method with a correlational design involving 52 respondents, determined using the Slovin formula from a population of 105 female students, with data collected through questionnaires that met validity and reliability tests and were analyzed using Pearson’s correlation test in SPSS version 22. The results indicate that price, online reviews, and consumer trust have a positive and significant correlation with purchasing decisions. This finding demonstrates that these three variables play an important role in influencing students’ decisions to purchase OMG Lipmatte products.